Hypoxia induces purinergic receptor signaling to disrupt endothelial barrier function - Raghavan, Somasundaram; Brishti, Masuma Akter; Collier, Daniel Mohr; Leo, M. Dennis (Frontiers in Physiology, 2022)
Blood-brain-barrier permeability is regulated by endothelial junctional proteins and is vital in limiting access to and from the blood to the CNS. When stressed, several cells, including endothelial cells, can release several nucleotides like ATP and ADP that signal through purinergic receptors on these cells to disrupt BBB permeability. While this process is primarily protective, unrestricted, uncontrolled barrier disruption during injury or inflammation can lead to serious neurological consequences. Purinergic receptors are broadly classified into two families: the P1 adenosine and P2 nucleotide receptors. The P2 receptors are further sub-classified into the P2XR ion channels and the P2YR GPCRs. While ATP mainly activates P2XRs, P2YRs have a broader range of ligand selectivity. The P2Y1R, essential for platelet function, is reportedly ubiquitous in its expression. Prior studies using gene knockout and specific antagonists have shown that these approaches have neuroprotective effects following occlusive stroke. Here we investigated the expression of P2Y1R in primary cultured brain endothelial cells and its relation to the maintenance of BBB function. Results show that following in vitro hypoxia and reoxygenation, P2Y1R expression is upregulated in both control and diabetic cells. At the same time, endothelial junctional markers, ZO-1 and VE-cadherin, were downregulated, and endothelial permeability increased. siRNA knockdown of P2Y1R and MRS 2500 effectively blocked this response. Thus, we show that P2Y1R signaling in endothelial cells leads to the downregulation of endothelial barrier function.